ADVANCED ACCOUNTANCY VOL - I - JAIN S P; K L NARANG; SIMMI AGARWAL; MONIKA SEHGAL (LUDHIANA KALYANI, 2023)
"Advanced Accountancy, Vol. 1" by S.P. Jain and K.L. Narang has been a cornerstone textbook for commerce and accounting students across India. Published by Kalyani Publishers, this comprehensive volume has guided countless students through the foundational and advanced principles of accounting. The book is often co-authored in its recent editions by Simmi Agrawal and Monika Sehgal, reflecting its continuous updates to keep pace with the evolving accounting landscape.
ACCOUNTING
BBA & MBA
Keywords: ACCOUNTING; MANAGEMENT